The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12881-015-0259-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, smoking, and genetic predisposition to obesity in people from Pakistan: the PROMIS study

Abstract: BackgroundMultiple genetic variants have been reliably associated with obesity-related traits in Europeans, but little is known about their associations and interactions with lifestyle factors in South Asians.MethodsIn 16,157 Pakistani adults (8232 controls; 7925 diagnosed with myocardial infarction [MI]) enrolled in the PROMIS Study, we tested whether: a) BMI-associated loci, individually or in aggregate (as a genetic risk score - GRS), are associated with BMI; b) physical activity and smoking modify the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
(36 reference statements)
1
26
1
Order By: Relevance
“…A number of gene × smoking interactions were identified when African Americans and Caucasians were analysed separately, but no significant interactions were observed in the overall sample from the Southern Community Cohort Study [167]. Four nominally significant gene × smoking interactions were reported in a recent study of 16157 Pakistani adults, with current smoking status amplifying the effect of PTBP2 rs11165643, HIP1 rs1167827 and GRID1 rs7899106 SNPs, and decreasing the effect of C6orf106 rs205262 SNP [120].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 83%
“…A number of gene × smoking interactions were identified when African Americans and Caucasians were analysed separately, but no significant interactions were observed in the overall sample from the Southern Community Cohort Study [167]. Four nominally significant gene × smoking interactions were reported in a recent study of 16157 Pakistani adults, with current smoking status amplifying the effect of PTBP2 rs11165643, HIP1 rs1167827 and GRID1 rs7899106 SNPs, and decreasing the effect of C6orf106 rs205262 SNP [120].…”
Section: Obesity-predisposing Gene Variants Interact With Smoking Statusmentioning
confidence: 83%
“…Gene-environment interaction plays an essential role in the determinant of complex trait/disease. For example, several studies have indicated that the estimated effective size of the risk alleles for obesity is more pronounced in smokers and individuals with a low physical activity [40-42]. In the Chinese population, lifestyle factors (such as smoking and less physical activity, etc.)…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…These GWAS and subsequent transferability studies performed in diverse populations from around the world have identified gene risk variants associated with human obesity (Hester et al, 2012; Ahmad et al, 2015; Hagg et al, 2015; Locke et al, 2015; Abadi et al, 2016). The sample data consists of 110 human obesity genes (56 obesity genes with ancestral risk variants and 54 obesity genes with derived risk variants).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the molecular basis of common obesity that has reached epidemic proportions in the United States and other developed countries, a large number of genome-wide association studies (GWAS) have been performed to identify obesity gene risk variants that increase susceptibility to this metabolic disease (Meyre et al, 2009; Thorleifsson et al, 2009; Willer et al, 2009; Scherag et al, 2010; Speliotes et al, 2010; Kilpelainen et al, 2011; Bradfield et al, 2012; Wen et al, 2012; Berndt et al, 2013; Bian et al, 2013; Monda et al, 2013; Locke et al, 2015; Minster et al, 2016). These GWAS and subsequent transferability studies performed in different populations around the world have now validated 110 human obesity genes with 127 nearest obesity gene risk variants (Hester et al, 2012; Ahmad et al, 2015; Hagg et al, 2015; Locke et al, 2015; Abadi et al, 2016). It is generally accepted that the obesity epidemic is a recent manifestation that has occurred during the past few decades and not all individuals or populations are adversely affected, thereby suggesting individual differences based on genetic variability and interactions with an obesogenic environment (Nakamura et al, 2015; Nettleton et al, 2015; Reddon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%